Antimicrobial Compounds from the Shoots of Arctotis Arctotoides - Sultana, Nasim; Afolayan, AJ; Bhuiyan, Rauf Ahmed (Bangladesh Journal of Scientific and Industrial Research, 2008)
Arctotis arctotoides is a perennial herb used medicinally for the treatment of various ailments in the Eastern Cape, South Africa. Different extracts from the shoots of this herb showed antimicrobial activity against some bacterial species. Bioassay guided fractionation of the extracts has led to the isolation of three compounds, glycerol-1- docosanoate, zaluzanin C and perydiscolic acid. The structures were elucidated on the basis of their one- and two-dimensional NMR spectral analysis and by a comparative literature study. The evaluation of antimicrobial activity of the compounds revealed moderate activity against four Gram-positive and two Gram-negative bacteria. Keywords: Arctotis arctotoides, Asteraceae, Antibacterial activity, Glycerol-1- docosanoate, Zaluzanin C, Perydiscolic acid. DOI: 10.3329.bjsir.v43i1.860 Bangladesh J. Sci. Ind. Res. 43(1), 89-96, 2008